Aktivitas Antioksidan dan Total Fenolik Rumput Laut Gracilaria sp. Kabupaten Brebes: Antioxidant Activity and Total Phenolic Of Seaweed Gracilaria sp. from Brebes - Rifatul Masrikhiyah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2021)
Brebes regency is one of the seaweed producing areas in Central Java province with an area of seaweed ponds as much as 4,350 ha of the total pond area of 12,748 ha that produces 200 tons of dried seaweed per month. Seaweed can be used as a source of antioxidants because it contains bioactive compounds especially for phenolic compounds, flavonoids and alkaloids. The purpose of this study is to examine the antioxidant activity and total phenolic powder of seaweed Gracilaria sp. from Brebes. The observed parameters are free radical capture capacity using DPPH radical scavenging activity (RSA) method and total phenolic using Folin-Ciocalteu method. This study used a Complete RandomIzed Design (RAL) consisting of 2 treatments (seaweed powder from fresh and dry raw materials) and conducted 3 repetitions. Gracilaria sp. Seaweed powder from fresh raw materials has a total phenol content and a higher free radical catching capacity compared to dry raw materials. The total content of seaweed powder phenol Gracilaria sp. from Brebes district is about 4.35–4.49 (mg GAE/100 g) and its antioxidant activity is about 15.90–42.50 (%RSA). There are differences in the capture capacity of free radicals using wet and dry seaweed raw materials.